POLY(GLYCIDYL METHACRYLATE-DIVINYLBENZENE) MONOLITHIC CAPILLARY AS A STATIONARY PHASE FOR THE REVERSED-PHASE CHROMATOGRAPHIC SEPARATION OF PROTEINS - Nurul Hidayat Aprilita; Rania Bakry; Christian W Huck; Guenther K Bonn (Universitas Gadjah Mada, 2005)
Capillary column with monolithic stationary phase was prepared from silanized fused-silica capillary of 200 µm I.D. by in situ free radical polymerization of divinylbenzene with glycidy methacrylate in the presence of decanol and tetrahydrofuran as porogens. The hydrodynamic and chromatographic properties of this monolith, such as backpressure at different flow-rate, pore size distribution, van Deemter plot and the effect of varying gradient-rate were investigated. Poly(glycidyl methacrylate-divinylbenzene) monolithic capillary has been used successfully for the reversed-phase chromatographic separation of proteins.